Monitoramento da qualidade das águas de chuvas conforme a atuação dos sistemas sinóticos na cidade de Natal/RN - Alves, Adriano Eduardo Lívio (2009)
Acid rain is a major assault on the environment, a consequence of burning fossil fuels and industrial pollutants the basis of sulfur dioxide released into the atmosphere. The objective of this research was to monitor and analyze changes in water quality of rain in the city of Natal, seeking to investigate the influence of quality on a local, regional and global, in addition to possible effects of this quality in the local landscape. Data collection was performed from December 2005 to December 2007. We used techniques of nefanálise in identifying systems sinóticos, field research in the search for possible effects of acid rain on the landscape, and collect and analyze data of precipitation and its degree of acidity. Used descriptive statistics (standard deviation and coefficient of variation) used to monitor the behavior of chemical precipitation, and monitoring of errors in measurements of pH, level of confidence, Normalized distribution of Gauss, confidence intervals, analysis of variance ANOVA were also used. Main results presented as a variation of pH between 5,021 and 6,836, with an average standard deviation of 5,958 and 0,402, showing that the average may represent the sample. Thus, we can infer that, according to the CONAMA Resolution 357 (the index for fresh water acidity should be between 6.0 and 9.0), the precipitation of Natal / RN is slightly acidic. It appears that the intertropical convergence zone figures showed the most acidic among the systems analyzed sinóticos, taking its average value of pH of 5,617, which means an acid value now, with a standard deviation of 0,235 and the coefficient of variation of 4,183% which shows that the average may represent the sample. Already in field research and found several places that suffer strongly the action of acid rain. However, the results are original and need further investigation, including the use of new methodologies